2021
DOI: 10.3390/jcm10194316
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of Glenoid Concavity—Bony and Osteochondral Assessment of a Stability-Related Parameter

Abstract: Glenoid concavity is a crucial factor for glenohumeral stability. However, the distribution of this stability-related parameter has not been focused on in anatomical studies. In this retrospective study, computed tomography (CT) data and tactile measurements of n = 27 human cadaveric glenoids were analyzed with respect to concavity. For this purpose, the bony and osteochondral shoulder stability ratio (BSSR/OSSR) were determined based on the radius and depth of the glenoid shape in eight directions. Various st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…One possible explanation for the decreasing stability during cartilage loss is that the concavity of the glenoid is essentially built up by the cartilage [ 33 ]. This was confirmed by the fact that the concavity gradient decreased with each further state of induced cartilage loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the decreasing stability during cartilage loss is that the concavity of the glenoid is essentially built up by the cartilage [ 33 ]. This was confirmed by the fact that the concavity gradient decreased with each further state of induced cartilage loss.…”
Section: Discussionmentioning
confidence: 99%
“…A layer of cartilage is deposited on the glenoid bone, increasing in thickness from the centre to the outer rim [ 15 ]. This cartilage layer increases the concavity gradient and concavity compression in addition to the concave shape of the bone [ 33 ]. In case of recurrent dislocations, higher grade loss of cartilage is reported [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…30,50 However, we found that once the traumatic instability occurred, the deeper native glenoid instead was associated with a more severe structural lesion because it is associated with deeper, wider, and more medialized HSL. Together with the previous finding that the loss of stability for a given level of bone loss is positively associated with native glenoid depth, 30,49,50 a deep native glenoid frequently results in a conspicuous decrease in both midrange stability 30,50,51 produced by glenoid defects and end-range stability 21 induced by humeral defects in the context of bipolar bone loss. Additionally, this study can aid in a quick comprehension of the 3D properties of HSL.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have described the biomechanical relationship between the 3D shape of the glenoid and the Linear (1-dimensional) BFC diameter 0.8 (0.5-0.9) Substantial 0.9 (0.7-1.0) Almost perfect Defect diameter 0.8 (0.7-0.9) Substantial 0.9 (0.9-1.0) Almost perfect Ratio 0.8 (0.7-0.9) Almost perfect 0.9 (0.9-1.0) Almost perfect Area (2-dimensional) BFC area 0.8 (0.4-0.9) Substantial 0.9 (0.7-1.0) Almost perfect Defect area 0.8 (0.6-0.8) Substantial 0.9 (0.9-1.0) Almost perfect Ratio 0.8 (0.7-0.9) Substantial 0.9 (0.8-0.9) Almost perfect Concavity (3-dimensional) BSSR 0.5 (0.2-0.7) Moderate 0.9 (0.9-0.9) Almost perfect a stability ratio. 9,11,12,17,27 Furthermore, Moroder et al 16,17 emphasized the differences in glenoid morphology between patients and challenged the current concept of defining a general threshold for a critical glenoid defect. In their finite element analysis, they showed a nonlinear relationship between the glenoid defect size and its biomechanical effect and differences in biomechanically relevant glenoid concavity between patients.…”
Section: Discussionmentioning
confidence: 99%